A Systematic Review of Neuromonitoring Modalities in Children Beyond Neonatal Period After Cardiac Arrest*. Issue 10 (October 2020) - Hunfeld, Maayke; Ketharanathan, Naomi; Catsman, Coriene; Straver, Dirk C. G.; Dremmen, Marjolein H. G.; Bramer, Wichor; Wildschut, Enno; Tibboel, Dick; Buysse, Corinne
Abstract : Objectives: Postresuscitation care in children focuses on preventing secondary neurologic injury and attempts to provide (precise) prognostication for both caregivers and the medical team. This systematic review provides an overview of neuromonitoring modalities and their potential role in neuroprognostication in postcardiac arrest children. Data Resources: Databases EMBASE, Web of Science, Cochrane, MEDLINE Ovid, Google Scholar, and PsycINFO Ovid were searched in February 2019. Study Selection: Enrollment of children after in- and out-of-hospital cardiac arrest between 1 month and 18 years and presence of a neuromonitoring method obtained within the first 2 weeks post cardiac arrest. Two reviewers independently selected appropriate studies based on the citations. Data Extraction: Data collected included study characteristics and methodologic quality, populations enrolled, neuromonitoring modalities, outcome, and limitations. Evidence tables per neuromonitoring method were constructed using a standardized data extraction form. Each included study was graded according to the Oxford Evidence-Based Medicine scoring system. Data Synthesis: Of 1, 195 citations, 27 studies met the inclusion criteria. There were 16 retrospective studies, nine observational prospective studies, one observational exploratory study, and one pilot randomized controlled trial. Neuromonitoring methods included neurologic examination, routine electroencephalography and continuous electroencephalography, transcranial Doppler, MRI, head CT, plasma biomarkers, somatosensory evoked potentials, and brainstem auditory evoked potential. All evidence was graded 2B-2C. Conclusions: The appropriate application and precise interpretation of available modalities still need to be determined in relation to the individual patient. International collaboration in standardized data collection during the (acute) clinical course together with detailed long-term outcome measurements (including functional outcome, neuropsychologic assessment, and health-related quality of life) are the first steps toward more precise, patient-specific neuroprognostication after pediatric cardiac arrest. Abstract : Supplemental Digital Content is available in the text.